The Influence of Science Textbooks on Simple Machines Based on Local Wisdom on Students' Learning Outcomes: Pengaruh Buku Ajar Ipa Materi Usaha Dan Pesawat Sederhana Berbasis Kearifan Lokal Terhadap Hasil Belajar Siswa - Rakhmawati , Ariningtyas Dwi; Wulandari, Fitria Eka (Indonesian Journal of Education Methods Development, 2023)
This quantitative study investigates the impact of incorporating local wisdom into science textbooks, combined with simple aircraft projects, on student learning outcomes. Using a pre-experimental design with one experimental and two replication classes, eighth-grade students from a local school were assessed using a cognitive learning test before and after the intervention. The N-Gain test revealed an average N-Gain score of 0.3 across all classes, with a significant p-value of 0.000, indicating a substantial improvement in student learning outcomes. The findings underscore the moderate positive effect of science textbooks infused with local wisdom on enhancing student learning. This research contributes to the ongoing discourse on pedagogical approaches that leverage cultural contexts to optimize educational outcomes. Highlights: Innovative Pedagogy: Integrating local wisdom into science textbooks offers an innovative approach to enhance student learning outcomes by connecting academic content with cultural relevance. Quantitative Impact Analysis: Through a pre-experimental design, the study quantitatively demonstrates the positive effect of incorporating local wisdom and hands-on aircraft projects on student cognitive growth. Cultural Contextualization: The research underscores the significance of contextualizing educational materials within the cultural framework, thereby fostering a deeper understanding and engagement among students. Keywords: Science education, Local wisdom, Student learning outcomes, Textbook enhancement, Cultural integration